EXPLORING THE DIFFERENCES BETWEEN BUDGET ACCOUNTING IN THE PUBLIC SECTOR AND ACCOUNTING IN THE PRIVATE SECTOR (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the differences in measurement bases and techniques between International Financial Reporting Standards (IFRS) and International Public Sector Accounting Standards (IPSAS). The analysis identifies three key differences that warrant closer examination: the application of fair value in the public sector, the unique measurement basis of current operational value, and the treatment of assets held for their service potential and other specialized assets. Furthermore, the comparison of budget accounting practices in the public and private sectors highlights challenges and opportunities for aligning financial reporting practices.